THE PRINCIPAL'S STRATEGY IN IMPROVING POSITIVE CULTURE FOR THE EFFECTIVENESS OF SDN KALIREJO 02 - dyah ayu permatasari; AY Soegeng Ysh; ngurah ayu nyoman murniati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the principal’s strategic planning in cultivating a Positive Culture to enhance the overall effectiveness of SDN Kalirejo 02. Employing a qualitative case study design, data were gathered through observations, in-depth interviews, and document analysis involving principals, teachers, students, parents, and staff. The findings show that strategic planning is implemented through three interconnected phases: Strategy Formulation, Strategy Implementation, and Strategy Evaluation. Strategy Formulation emphasizes context diagnosis, identification of core cultural values, and the development of SMART goals focusing on discipline improvement, teacher attendance, and student learning motivation. Strategy Implementation includes teacher capacity development, restructuring the learning environment, and strengthening positive routines. The principal plays a central role as a role model and motivator in mobilizing stakeholders. Evaluation is conducted adaptively using quick-win monitoring, periodic climate surveys, and PDCA-based feedback loops. The study concludes that the strategic planning implemented at SDN Kalirejo 02 effectively integrates Positive Culture principles, leading to measurable behavioral improvements and enhanced academic and non-academic performance.